TikTok Content Analysis on Perceptions of Masculinity: A Case Study of @ZAAFERINDONESIA - Aliifa Nazlizasandi; Khaerudin Imawan; Rahmayanti (Athena: Journal of Social, Culture and Society, 2026)
Fashion serves as a social communication and influence-presentation tool that reflects the culture, values, social habits and even the profession of people. Among Muslim Men's Clothing we have particularly garment elements that are used to construct an image of powerful and dominating masculinity. The aim of this research is TikTok account analysis @zaaferindonesia, a Muslim man fashion brand. Through the use of Roland Barthes Semiotics that is applied to their visual marketing, Zaafer Indonesia constructs a masculinity imagery. Data was collected by analyzing the brand’s social media posts, particularly those that included men in flashy environments wearing black Thawb. The researchers’ analysis shows that the thawb's black color is loaded with connotative meanings of strength, grace and authority, while vibrant purple background enhances associations with success and high social status. This indoctrination promotes a myth that, ala Muslim style, real manliness is associated with being bold, assertive and top gun. The findings of the research indicate that representations of Muslim fashion are suggestive, not only about aesthetics for both men and women, but also gendering practices, social identity and difference. Learn how semiotics in branding strategies can assist the fashion industry to build an image that corresponds with the target market's values and tastes.